Application of Transgenic Zebrafish Models for Studying the Effects of Estrogenic Endocrine Disrupting Chemicals on Embryonic Brain Development - Takesono, Aya; Kudoh, Tetsuhiro; Tyler, Charles R. (Frontiers in Pharmacology, 2022)
Endocrine disrupting chemicals (EDCs) are environmental pollutants that mimic hormones and/or disrupt their function. Estrogenic EDCs (eEDCs) interfere with endogenous estrogen signalling pathway(s) and laboratory animal and human epidemiological studies have provided evidence for a causal link between exposure to them during embryonic/early life and neurological impairments. However, our understanding of the molecular and cellular mechanism(s) underlying eEDCs exposure effects on brain development, tissue architecture and function and behaviour are limited. Transgenic (TG) zebrafish models offer new approach methodologies (NAMs) to help identify the modes of action (MoAs) of EDCs and their associated impacts on tissue development and function. Estrogen biosensor TG zebrafish models have been applied to study eEDC interactions and resulting transcriptional activation (via a fluorescent reporter expression) across the entire body of the developing zebrafish embryo, including in real time. These estrogen biosensor TG zebrafish models are starting to deepen our understanding of the spatiotemporal actions of eEDCs and their resulting impacts on neurological development, brain function and behaviour. In this review, we first investigate the links between early life exposure to eEDCs and neurodevelopmental alterations in model organisms (rodents and zebrafish) and humans. We then present examples of the application of estrogen biosensor and other transgenic zebrafish models for elucidating the mechanism(s) underlying neurodevelopmental toxicities of eEDCs. In particular we illustrate the utility of combining estrogen biosensor zebrafish models with other TG zebrafish models for understanding the effects of eEDCs on the brain, spanning cellular processes, brain circuitry, neurophysiology and behaviour. Finally, we discuss the future prospects of TG zebrafish models as experimental models for studying more complex scenarios for exposure to contaminant mixtures on neurological development and function.